Pengaruh Layanan Mobile Banking Terhadap Loyalitas Nasabah - Rizki Chaerunisa, Danya; Pranata, Sudadi; Laily Purnamasari, Dewi (Awatara Publisher, 2025)
This study aims to analyze the effect of mobile banking services on customer loyalty in Indonesia's state-owned banks (BUMN). Mobile banking is a form of digital innovation that offers convenience, efficiency, and speed in banking transactions. Using a quantitative approach, data were collected from 100 respondents who are active users of mobile banking services from BUMN banks via an online questionnaire. The results of the regression analysis indicate that mobile banking services have a positive and significant effect on customer loyalty, with a coefficient value of 0.319 and a significance level of 0.000. This finding suggests that the higher the perceived quality of mobile banking services, the greater the customer loyalty. The study supports the Expectation Confirmation Theory (ECT) and provides practical contributions for bank management in developing digital service strategies oriented toward customer satisfaction and loyalty. This research also opens opportunities for further exploration of mediating variables such as customer satisfaction or trust to gain a deeper understanding of loyalty-building factors in the digital banking era.